Assessing aquitard hydraulic performance from hydrocarbon migration indicators: Surat and Bowen basins, Australia. (December 2016) - Underschultz, J.R.; Pasini, P.; Grigorescu, M.; de Souza, T.L.
Abstract: Basin hydrodynamic assessment methods are being applied to Australia's developing coal seam gas (CSG) to liquefied natural gas (LNG) export developments in the Queensland's Bowen and Surat basins. Technical challenges include the need to predict the cumulative impacts of CSG production on formation pressure in adjacent Great Artesian Basin aquifers and assess to what degree, if any, there may be fugitive methane liberated from the reservoir but not captured by production wells. Both these challenges require an understanding of the distribution of aquitard hydraulic sealing performance. We use hydrocarbon systems analysis to illuminate basin scale geological seal performance of the low permeability strata and provide baseline data on hydrocarbons in groundwater. We collected indicators of hydrocarbons including: 1) drill stem, wireline and production test sample analysis, 2) staining, fluorescence, and streaming hydrocarbon occurrences from drill cuttings and core, and 3) mud log gas detector data. This data was allocated to stratigraphic horizons, mapped and compared to the geographic/stratigraphic location of source rocks, conventional and unconventional reservoired hydrocarbons, and aquitard/sealing strata and faults. We found asymmetric trapping of conventional hydrocarbon reservoirs with eastern basin leakage and western basin preservation. Indications of some thermogenic gas in the Walloon Coal Measures exist yet maturity indicators are sub-thermogenic, suggesting that although much of the Walloon Coal Measures gas is biogenic, thermogenic gas may have previously migrated into the Walloon Coal Measures from elsewhere. Stratigraphically below the Walloon Coal Measures, hydrocarbon migration indicators are often clustered along lineations such as the Moonie-Goondiwindi and Burunga-Leichhardt fault systems. At the top of the Walloon Coal Measures, hydrocarbon migration indicators are clustered along the northeastern subcrop edge of the basin where the muddy strata at the top are either thin or eroded suggesting vertical leakage occurred to the overlying Springbok Sandstone aquifer. Whilst we can see where seals are either more, or less effective, at this stage we cannot make a quantitative assessment of background methane flux to surface or potential future proportional allocation of methane flux to natural vs anthropogenic causes. Highlights: Asymmetric trapping of conventional hydrocarbon reservoirs with eastern leakage and western preservation. Thermogenic gas in the Walloon Coal Measures yet vitrinite reflectance suggest it is immature for gas generation. Hydrocarbon migration indicators (gas and oil shows) are present all the way to surface. NE edge of the Walloon Coal Measures shows evidence of vertical hydrocarbon leakage into the overlying Springbok Sandstone. Hydrocarbon leakage indicators are clustered along the Moonie-Goondiwindi and Burunga-Leichhardt and other fault systems.